If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -0.3x + 5.36 = -0.1x + 0.56 Reorder the terms: 5.36 + -0.3x = -0.1x + 0.56 Reorder the terms: 5.36 + -0.3x = 0.56 + -0.1x Solving 5.36 + -0.3x = 0.56 + -0.1x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '0.1x' to each side of the equation. 5.36 + -0.3x + 0.1x = 0.56 + -0.1x + 0.1x Combine like terms: -0.3x + 0.1x = -0.2x 5.36 + -0.2x = 0.56 + -0.1x + 0.1x Combine like terms: -0.1x + 0.1x = 0.0 5.36 + -0.2x = 0.56 + 0.0 5.36 + -0.2x = 0.56 Add '-5.36' to each side of the equation. 5.36 + -5.36 + -0.2x = 0.56 + -5.36 Combine like terms: 5.36 + -5.36 = 0.00 0.00 + -0.2x = 0.56 + -5.36 -0.2x = 0.56 + -5.36 Combine like terms: 0.56 + -5.36 = -4.8 -0.2x = -4.8 Divide each side by '-0.2'. x = 24 Simplifying x = 24
| 11+11b=66 | | n(3+7)+2=92 | | 4x-10=9x-6 | | 2(w-3)-1=-3(-7w+1)-9w | | 12(0.5n+2)=36 | | X^2=60+8x | | 20b+15s+22t=735 | | 24+3d-10h+8d=0 | | 800x-0.71=600x+0.79 | | 5x-5+11+11x=70 | | 8(n-9)=80 | | -87=6x-3 | | 2.3x-35=1.1x+7 | | 5(2n-5)=26 | | 3+3x^2=15 | | 5.4x+8-3.4x=2 | | X^2-6x=2x+60 | | 7x+10y=51 | | 5.4+8-3.4x=2 | | 8(a+2)+3=2(a-4)-11 | | 2/7y-5=-9 | | -7(y+1)=3y-9+2(4y+6) | | 0.5[7d+4]=7-1.5d | | 6x-31.5=x | | 1.6s=20 | | 20-14k+20=-9k-20 | | X*2-6x=2x+60 | | 15s+20b+22t=735 | | 74-y=187 | | -2(-5x-4)-2x-1=-1 | | 3(x-4.3)=6.3 | | 5x-3(4x-8)= |